The BinaMIcS project: understanding the origin of magnetic fields in massive stars through close binary systems. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Alecian, E.; Neiner, C.; Wade, G. A.; Mathis, S.; Bohlender, D.; Cébron, D.; Folsom, C.; Grunhut, J.; Le Bouquin, J.-B.; Petit, V.; Sana, H.; Tkachenko, A.; et al.
Abstract: It is now well established that a fraction of the massive ( M > 8 M ⊙ ) star population hosts strong, organised magnetic fields, most likely of fossil origin. The details of the generation and evolution of these fields are still poorly understood. The BinaMIcS project takes an important step towards the understanding of the interplay between binarity and magnetism during the stellar formation and evolution, and in particular the genesis of fossil fields, by studying the magnetic properties of close binary systems. The components of such systems are most likely formed together, at the same time and in the same environment, and can therefore help us to disentangle the role of initial conditions on the magnetic properties of the massive stars from other competing effects such as age or rotation. We present here the main scientific objectives of the BinaMIcS project, as well as preliminary results from the first year of observations from the associated ESPaDOnS and Narval spectropolarimetric surveys.